COMBINING ABILITY OF INBRED LINES DERIVED FROM A YELLOW FLINT MAIZE SYNTHETIC CMS 53 - GAMA, ELTO EUGENIO GOMES E; MEIRELES, WALTER FERNANDES; GUIMARÃES, PAULO EVARISTO; FERRÃO, ROMÁRIO GAVA; PARENTONI, SIDNEY NETO; PACHECO, CLESO ANTÔNIO PATTO; SANTOS, MANOEL XAVIER DOS; OLIVEIRA, ANTÔNIO CARLOS DE (International Journal of Maize & Sorghum, 2010)
<!--[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <mce:style><! st1\:*{behavior:url(#ieooui) } --> <!--[endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} --> <!--[endif]--> The objectives were to study the combining ability of lines, derived from synthetic maize (Zea mays L.) CMS 53, in a diallel crosses, to identify lines for developing more stable and superior yielding hybrids combinations with a dent heterotic group. The 9 inbreds were crossed to form 36 single crosses, in 1999. Parental inbreds and crosses together with a single cross commercial hybrid were evaluated using a randomized complete block design with 2 replications in four locations during the 1999/00 summer season. Data were collected for several agronomic traits, but only ear yield (kg/ha) is discussed. For the analysis of this trait, Griffing´s (1956) method 2, was used. The combining ability showed highly significant (P< 0.01) effects for locations, crosses, lines, general combining ability (GCA), and specific combining ability (SCA). Genotype x Locations was highly significant, but SCA x Location was (P< 0.05) significant. Means of the crosses over locations ranged from 6678kg/ha to 11122kg/ha. Results showed that additive and non-additive gene effects were important in this diallel study. There were specific superior crosses for each location indicating the importance of SCA effects over GCA effects at all locations. The selected lines should be useful to a breeding program in tropical conditions.